Application of the Everyone is A Teacher Here Learning Strategy to Elementary-aged Students - Nina Aldila Berutu (Yayasan Zia Salsabila, 2023)
This study aims to analyze the results of applying the everyone is a teacher here learning strategy to students of class V MIN 12 Medan City. This study uses a descriptive qualitative research method that aims to describe an object, phenomenon, or problem with the facts being studied. Data collection techniques were carried out using observation techniques, interviews, and documentation studies. The results of the research on students in class V MIN 12 Medan City, namely: (1) students can work together well, (2) students can write questions that are appropriate to the learning material (3) students dare to appear in front of the class in answering questions from other groups. The application of the everyone is a teacher here learning strategy can be implemented properly because there is a significant increase in student learning outcomes. Students become more active in learning because the strategies used can attract students' interest and attention in learning. Thus, learning by applying the everyone is a teacher here strategy gets a positive response from students so that it is feasible to be implemented by the teacher.